THE IMPACT OF THE INTENSITY OF USING MOBILE PHONES AMONG ELEMENTARY SCHOOL CHILDREN IN UMBULHARJO DISTRICTS YOGYAKARTA - Sriwiyata Sriwiyata (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research was supported by the assumption that elementary school children did not use mobile phones for doing assignments but they used mobile phones for entertainment activities. The research was conducted by distributing questionnaires and conducting interviews with respondents in 3 areas, namely Desa Semaki, Warungboto, and Mujamuju in Yogyakarta. Based on the results of this research,it turned out that the use of handphones among elementary school children in Kecamatan Umbulharjo, Yogyakarta was still good or reasonable. The children used mobile phones to do the school assignments everyday. When they felt bored in doing their assignments, they switched to use the mobile phone for entertainment activities, such as playing games with their friends. The results of the research in the field revealed that the samples were 30 students taken from 1724 respondents. Thus, the intensity of using mobile phones among elementary school children were high in order to improve their achievement. This was proven by the results of data analysis which obtained a percentage of 57.8% .